Pronunciation Errors in Syllabic Consonants (An Investigation of the Student's Phonological Understanding) - Nirwana (Universitas Islam Ahmad Dahlan (UIAD), 2021)
This research examined pronunciation errors in syllabic consonant sounds uttered by fourth-semester students in the English and literature departments. This study aimed to find out how fourth-semester students read the text and pronounce syllabic consonant sounds. The theories of English phonetics and phonology were proposed by Peter Roach and Corder's theory of error analysis. The data was gathered using the descriptive qualitative method. The researcher used the phone as an instrument to record herself reading aloud text. According to the findings, the students made three errors: addition, omission, and selection. First, they began using the schwa sound with long syllabic consonant words. Second, some syllables were removed, which was most common in the final syllable. Third, they identified where a syllable in a word should go because they heard a vowel sound that should not be there or a sound in a syllable that was in the wrong location. This mistake occurs in the middle and last syllables